2011
DOI: 10.1007/s10211-011-0094-9
|View full text |Cite
|
Sign up to set email alerts
|

The fitness of the Brazilian damsel Stegastes fuscus is increased by sharing the territory with the dusky grouper Epinephelus marginatus

Abstract: Stegastes fuscus and Epinephelus marginatus are known for co-habiting shelters. The damselfish S. fuscus uses the territory for nesting and must protect its eggs from grazers; the grouper E. marginatus is an omnivorous sitand-wait predator. This study aims to evaluate the effect of juvenile groupers on the reproductive success of the Brazilian damsel. Twenty-five hours of underwater observations were done in São Sebastião and Ilhabela, Northern shore of São Paulo, Brazil. Fitness increase was measured by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…This cladogram was organized using the previously published work of Rabosky et al (2018) and Betancur-R. et al (2013) major Abudefduf saxatilis are easily found by predators, hence nesting males spend more time averting egg predators than Chromis multilineata (Pomacentridae), another pomacentrid that conceals eggs amid algae (Bessa & Sabino, 2012). A cooperative interaction between Stegastes fuscus damsels and the dusky grouper (Epinephelus marginatus, Serranidae) was reported, in which the damsel benefits from sharing its territory with a grouper because this serranid feeds on egg predators attracted by the nest (Bessa, 2011). Finally, predatory fishing also benefits from knowing nesting habits.…”
Section: Cos Ts and Con S Tr Aints Of Ne S Tingmentioning
confidence: 99%
“…This cladogram was organized using the previously published work of Rabosky et al (2018) and Betancur-R. et al (2013) major Abudefduf saxatilis are easily found by predators, hence nesting males spend more time averting egg predators than Chromis multilineata (Pomacentridae), another pomacentrid that conceals eggs amid algae (Bessa & Sabino, 2012). A cooperative interaction between Stegastes fuscus damsels and the dusky grouper (Epinephelus marginatus, Serranidae) was reported, in which the damsel benefits from sharing its territory with a grouper because this serranid feeds on egg predators attracted by the nest (Bessa, 2011). Finally, predatory fishing also benefits from knowing nesting habits.…”
Section: Cos Ts and Con S Tr Aints Of Ne S Tingmentioning
confidence: 99%
“…Serranidae ( i.e ., groupers and sea basses) are considered key marine teleost fishes, playing a crucial role as predators and mesopredators, and maintaining ecosystem structure, functioning and resilience (Baum & Worm, 2009; Bessa, 2011; Burkholder et al ., 2013). Groupers and sea basses inhabit diverse habitats of the reef ecosystems ( e.g ., unconsolidated substrates, coral and rocky reefs), most commonly in depths <200 m (Anderson et al ., 2014, 2019).…”
Section: Introductionmentioning
confidence: 99%